Influências do teletrabalho na qualidade de vida no trabalho e na saúde mental de profissionais de recursos humanos de uma empresa varejista durante a pandemia de COVID-19 - Alves, Lanna Schellyda dos Santos (Brasil, 2022)
The pandemic of COVID-19 reverberates in all the aspects of people’s lives worldwide, and one of those is the work aspect. The infection by the virus SARS-CoV-2 spread on a global scale and in a short time influenced emergency health measures to contain its dissemination, which has a considerable responsibility for the chaos in the health care and economic system around the world. Among the contingency measures adopted are the social distancing to avoid crowds, the lockdown to decrease the level of circulation of people on the streets, maintaining only essential activities running and quarantine for the ones who got infected, seeking to decrease the contamination. In order to keep their activities running and their profits, the companies and employees adopted the emergency remote work, to do the work activities from home. This research aims to investigate how telecommuting in a pandemic context influences the quality of life on the teleworking and mental health care of the employees from the Human Resources. The choice of the target audience took into consideration the important role that these employees exercise towards the companies’ interests and the wellbeing of the other employees, in the public and private institutions. The study field was a large sales company based in Manaus. The research can be defined as descriptive and exploratory, the technical procedures of data collecting were performed in two phases, the first one was through the online application of a sociodemographic questionnaire and two Likert Scales: Quality of Life on the Compulsory Teleworking Scale and Mental Health on the Compulsory Teleworking Scale; the second one as a selection of volunteers to be interviewed individually. Due to the still ongoing pandemic, the scales were adapted to the Google Forms tool, sent by e-mail and WhatsApp to the employees of the sector. The interviews were performed according to the availability of the volunteers through Google Meet or in person, as long as all the security protocols are followed. For the data analysis, statistics and interpretation were used supported by the available literature, defining a quali-quantitative study.